The Concept of Nāfaqah in Islamic Law and Women's Right to Financial Support - Karimullah, Suud Sarim; Basuki, Nanda Ahmad; Sugitanata, Arif; Aminah, Siti (Program Studi Hukum Keluarga Islam Universitas Islam Negeri Raden Intan Lampung, 2024)
This study investigates how the concept of nafaqah is interpreted and applied in Muslim societies and how women's financial rights have been recognized and protected within the framework of Islamic law. The study utilizes the library research method as one of the main approaches to collecting relevant data and information from various perspectives and viewpoints. The analysis shows that although the concept of nafaqah is regulated in Islamic teachings, its implementation often does not reflect the principles of gender equality and economic justice. In addition, women's right to financial support is also an integral part of creating gender equality in society. These rights include women's inheritance rights, property ownership, and equal access to economic opportunities. As such, there is a need for concrete measures to strengthen the protection of women's financial rights in Muslim societies. This includes legal reforms recognizing women's economic rights equally, raising public awareness about the importance of gender equality in nafaqah, and promoting harmonization between the concept of nafaqah and women's economic rights.